Assistance in Handling Ergonomic Work Hazard Factors to Prevent MSDs in Informal Workers - Paskanita, Maria; Suratna, Farhana Syahrotun Nisa; Husna, Alifah Muti; Ardhia , Berliana; Kinasih, Eka Ayu Putri; Wibisono , Mario; Sulastri, Mia; Romadhona , Novita Dwi; Nur Arifin; Dzakiyatunisa, Raihana; Ardhana, Revan Wahyu; Rahmatulah, Suci (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Informal labour in the world is 57.8% according to ILO data in 2024. Indonesia has 59.11% proportion of informal employment in 2024 according to the Central Bureau of Statistics. Informal workers have hazardous factors that have not been identified and can cause injuries or occupational diseases. Informal cake-making workers who work 8 hours a day are potentially exposed to ergonomic hazards, fire hazards from cake baking and other occupational hazards. The purpose of this service is to provide knowledge and handling of occupational hazards in informal workers. The method of implementing community service is a field survey to identify hazards and risk assessments, conduct Strength, Weakness, Opportunity Treath (SWOT) analysis, Counselling and Poster Making. Community service produces data on the identification of occupational hazards and risk assessments of informal workers making cakes, ergonomics counselling materials and posters of safe work positions. Informal workers in the cake Home Industry have potential hazards of hand injury by machinery, potential fire hazards and potential hazards of skeletal muscle disorders in the form of Low back pain and Carpal Tunnel Syndrom. Knowledge of cake home industry workers regarding manual lifting and skeletal muscle disorders in workers has increased. Keywords: informal workers, ergonomics, poster